LITERATURE REVIEW: NEUROLOGICAL ASPECT OF CORONAVIRUS DISEASE 2019 (COVID-19): PART II. CLINICAL MANIFESTATIONS AND DRUG INTERACTIONS - Arthur H.P Mawuntu; Devina C Mastari; Albertus T Lapian; Agnes K.S. Hermawan; Mieke A.H.N Kembuan (Neurologi Manado, 2021)
Coronavirus disease 2019 (COVID-19) was first reported in China in December 2019. This novelvirus has caused a world health crisis with various clinical manifestations. Although the commonmanifestations of COVID-19 infection are fever, cough, malaise, and respiratory problems, there areincreasing reports of clinical manifestations and neurological complications such as decreasedconsciousness, headache, anosmia, stroke, seizures, polyneuropathy, and myopathy. The emergenceof neurological manifestations has prompted efforts to understand the COVID-19 therapies and thepotential drug interactions. Other issues discussed in other parts were pathomechanisms, druginteractions as well as disease effects in neurology patients. Understanding this may help manage thepatient